Interaction of Treponema pallidum with isolated rabbit capillary tissues. Issue 1 (February 1983) - Quist, E E; Repesh, L A; Zeleznikar, R; Fitzgerald, T J
Abstract : Within infected tissue Treponema pallidum shows a characteristic predilection for perivascular areas. After intact capillaries had been prepared from rabbit brain tissue treponemes were incubated with isolated capillaries and visualised by darkfield, phase contrast, and scanning electron microscopy. The organisms rapidly attached to the surface of the capillaries at the tip of the treponeme; attached organisms retained motility for longer periods than unattached organisms. Treponema pertenue also attached to capillaries. Heat-inactivated T pallidum and three non-pathogenic treponemes did not, however, attach to the capillaries. Immune rabbit serum contains a factor that blocks the attachment of T pallidum to capillaries. Compared with cultured mammalian cells capillaries should provide a better tool for investigating host-parasite relationships in syphilis.